Chap 24
Chap 24
Chap 24
3
1 −jωt
F (ω) = e dt
−3 4
1 −jωt 3
= − e −3
4jω
1 −3jωt
= − e − e3jωt
4jω
1
= sin 3ω
2ω
(b)
0
2
t t
F (ω) = e−jωt dt +
1+ 1− e−jωt dt
−2 2 0 2
0 0
t e−jωt 1 e−jωt
= 1+ − dt
2 −jω −2 −2 2 −jω
2 2
t e−jωt 1 e−jωt
+ 1− + dt
2 −jω 0 0 2 −jω
0
2
1 1 e−jωt 1 1 e−jωt
= − + +
−jω 2 −ω 2 −2 jω 2 −ω 2 0
1 1
= − 2 cos 2ω
ω2 ω
(c)
0 ∞
αt −jωt
F (ω) = e e dt + e−αt e−jωt dt
−∞ 0
∞ −(α+jω)t
∞
e(α−jω)t e
= +
α − jω −∞ −(α + jω) 0
1 1
= +
α − jω α + jω
2α
=
α2 + ω 2
(d) ∞
F (ω) = e−(1+jω)t cos t dt
0
Let
∞
I = e−(1+jω)t cos t dt
0
Pearson
c Education Limited 2001
Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual 221
∞ ∞
−(1+jω)t
= e (1 + jω) sin t e−(1+jω)t dt
sin t +
0
∞ ∞
0
−(1+jω)t −(1+jω)t
= (1 + jω) −e cos t − (1 + jω) cos t e dt
0 0
= (1 + jω) {1 − (1 + jω)I}
from which
1 + jω
F (ω) = I =
2 − ω 2 + 2jω
(e)
∞
F (ω) = e−t/τ e−jωt dt
0
∞
e−(jω+1/τ )t
=
−(jω + 1/τ ) 0
1
=
jω + 1/τ
τ
=
τ jω + 1
2.
∞
∞
e−(α+jω)t 1
F{u(t)e−αt } = e−(α+jω)t dt = =
0 −(α + jω) 0 α + jω
∞ −(s+α)t
∞
e 1
L{u(t)e−αt } = e−αt e−st dt = =
0 −(s + α) 0 s + α
Setting s = jω in the Laplace transform results in the Fourier transform.
3.
2
F{f (t)g(t)} = e(1−ω)jt dt
−2
2
e(1−ω)jt
=
j(1 − ω) −2
2(1−ω)j −2(1−ω)j
e e
= −
j(1 − ω) j(1 − ω)
2
= sin 2(1 − ω)
1−ω
Exercises 24.3
1. The first shift theorem. ∞
F{f (t)} = f (t)e−jωt dt = F (ω)
−∞
Pearson
c Education Limited 2001
222 Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual
∞
F{ejat f (t)} = f (t)ejat e−jωt dt
−∞
∞
= f (t)e−jt(ω−a) dt
−∞
= F (ω − a)
2.
1
F (ω) = (1 − t2 )e−jωt dt
−1
1 1 −jωt
(1 − t2 )e−jωt e
= − (−2t)dt
−jω −1 −1 −jω
1
2
= − te−jωt dt
jω −1
1 1 −jωt
2 te−jωt e
= − − dt
jω −jω −1 −1 −jω
2 2 cos ω e−jω − ejω
= − +
jω −jω ω2
4 sin ω 4 cos ω
= −
ω3 ω2
4 sin(ω − 3) 4 cos(ω − 3)
F (ω − 3) = −
(ω − 3)3 (ω − 3)2
(b) Let a = j:
4 sin(ω − j) 4 cos(ω − j)
F (ω − j) = −
(ω − j)3 (ω − j)2
Pearson
c Education Limited 2001
Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual 223
∞
F{f (t − α)} = f (z)e−jω(z+α) dz
z=−∞
∞
= e−jωα f (z)e−jωz dz
−∞
= e−jωα F (ω)
5.
1
f (t) = u(t)e−t , F (ω) =
1 + jω
f (t + 4) = u(t + 4)e−(t+4)
By the second shift theorem
e4jω
F{f (t + 4)} = e4jω F (ω) =
1 + jω
Exercises 24.4
0 1
F (ω) = (t + 1)e−jωt dt + e−jωt dt
−1 0
0 0 −jωt
1 1 −jωt
e−jωt e (1 − t)e−jωt e
= (t + 1) − dt + + dt
−jω −1 −1 −jω −jω 0 0 −jω
−jωt
0 −jωt
1
1 e 1 e
= + + −
−jω ω 2
−1 jω ω2 0
1 ejω e−jω 1
= 2
− 2 − 2 + 2
ω ω ω ω
2
= (1 − cos ω)
ω2
The pulse which would result if f (t) were passed through a filter which removed all angular frequencies greater
than 2π would be 2π
1 2
(1 − cos ω)ejωt dω
2π −2π ω 2
Pearson
c Education Limited 2001
224 Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual
Exercises 24.8
4
g(λ)
a)
f (λ)
-4 -3 -2 -1 0 1 2 3 4 λ
g(−λ) 4
b)
-4 -3 -2 -1 0 1 2 3 4 λ
c)
-4 -3 -2 -1 0 1 2 3 4 λ
-4 -3 -2 -1 0 1 2 3 4 λ
4
g(t − λ) when 2 < t < 3
e)
-4 -3 -2 -1 0 1 2 3 4 λ
4
g(t − λ) when 3 < t < 6
t−
f)
-4 -3 -2 -1 0 1 2 3 4
λ
4
g(t − λ) when t > 6
g)
-4 -3 -2 -1 0 1 2 3 4 λ
Pearson
c Education Limited 2001
Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual 225
When −1 < t < 2, (d), graphs overlap between 0 and 1 + t. Why ? When t = 0 g(t − λ) = g(−λ) as in b). For
t > 0, g(t − λ) is the graph in (b) translated t units to the right as in (d). Hence the overlap is between λ = 0
and λ = 1 + t.
1+t 1+t
2λ 4λ2 4(1 + t)2
f ∗g = 4 dλ = =
0 3 3 0 3
3
2λ 3
4λ2
for t > 2 but t < 3, (e), f ∗g = dλ =
4 = 12
0 3 3 0
3 3
2λ 4λ2 4
for t > 3 but t < 6, (f), 4 dλ = = 12 − (t − 3)2
t−3 3 3 t−3 3
When t > 6 the graphs do not overlap, (g), and f ∗ g = 0.
2. If t < −2, f ∗ f = 0.
If −2 < t < 0
t+1
t+1
f ∗f = f dλ = [t]−1
−1
= (t + 1) − (−1)
= t+2
If 0 < t < 2
1
1
f ∗f = f dλ = [t]−1+t
−1+t
= 1 − (−1 + t)
= 2−t
if t > 2, f ∗ g = 0.
Pearson
c Education Limited 2001
226 Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual
3.
a) f(λ)
1
λ
b)
1
g(λ)
λ
c)
g( λ− t ) when t < 0 1
t −1 1 λ
1
f g = e−(λ−t) dλ
−1
= e [−e−λ ]1−1
t
= et (e1 − e−1 )
if −1 < t < 1
1
f g = e−(λ−t) dλ
t
= et [−e−λ ]1t
= 1 − et−1
if t > 1 f g = 0.
dµ
Let µ = t − λ, i.e. λ = t − µ, = −1.
dλ
Pearson
c Education Limited 2001
Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual 227
Then
µ=−∞
f ∗g = f (t − µ)g(µ)(−dµ)
µ=∞
∞
= + g(µ)f (t − µ)dµ
−∞
∞
= + g(λ)f (t − λ)dλ since µ is a dummy
−∞
= g∗f as required
6. Convolution theorem:
∞ ∞
F{f ∗ g} = f (λ)g(t − λ)dλ e−jωt dt
−∞ −∞
−jωt
F{f ∗ g} = f (λ)g(t − λ)e dt dλ
−∞ −∞
∞ ∞
−jωt
= f (λ) g(t − λ)e dt dλ
−∞ −∞
as t→∞ µ→∞
t → −∞ µ → −∞
∞ ∞
−jω(µ+λ)
F{f ∗ g} = f (λ) g(µ)e dµ dλ
−∞ −∞
∞ ∞
−jωλ
= f (λ)e dλ g(µ)e−jωµ dµ
−∞ −∞
= F (w)G(w) as required
Pearson
c Education Limited 2001
228 Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual
7. ∞
f g = f (λ)g(λ − t)dλ
−∞
∞
f (t) g(t) = f (t) h(−t) = f (λ)h(t − λ)dλ
−∞
= f (t) ∗ h(t)
= f (t) ∗ g(−t) as required
And hence the convolution of f (t) and h(t) can be found by calculating the correlation of f (t) and g(t) where
g(t) = h(−t) and vice versa.
f (t) g(t) = f (λ)g(λ − t)dλ
f (t) g(−t) = f (λ)g(t − λ)dλ
8. ∞
f g = f (λ)g(λ − t)dλ
−∞
Let λ − t = µ, then
∞
f g = f (µ + t)g(µ)dµ (µ is a dummy variable)
−∞
∞
= g(λ)f (t + λ)dλ as required
−∞
9.
∞ ∞
∞ −∞
F {f g} = g(µ)e−jω(λ−µ) (−dµ) dλ
f (λ)
−∞ ∞
∞ ∞
−jωλ
= f (λ)e dλ g(µ)ejωµ dµ
−∞ −∞
Pearson
c Education Limited 2001
Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual 229
Now
∞
G(ω) = g(t)e−jωt dt
−∞
∞
G(−ω) = g(t)ejωt dt
−∞
So
F {f g} = F (ω)G(−ω) as required.
Exercises 24.9.1
1.
f [n] = 1, 2, 0, −1. N =4
3
F [k] = f [n]e−jnkπ/2
n=0
3
F [0] = f [n] = 1 + 2 + 0 + (−1) = 2.
n=0
F [1] = f [n]e−jnπ/2 = 1 + 2e−jπ/2 + 0 − 1e−j3π/2
= 1 − 2j − j
= 1 − 3j
F [2] = f [n]e−jnπ = 1 + 2(−1) + 0 − 1(−1)
= 1−2+1
= 0
F [3] = f [n]e−jn3π/2 = 1 + 2j + 0 − 1(−j)
= 1 + 2j + j
= 1 + 3j
g[n] = 3, 1, −1, 1. N =4
3
G[k] = g[n]e−jnkπ/2
n=0
G[0] = 3+1−1+1=4
G[1] = 3 + e−jπ/2 − 1e−jπ + 1e−3jπ/2
= 3−j+1+j
= 4
Pearson
c Education Limited 2001
230 Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual
2.
f [n] = 5, −1, 2 N =3
2
F [k] = f [n]e−2jnkπ/3
n=0
F [0] = f [n] = 6
F [1] = f [n]e−2jnπ/3
= 5 − 1e−2jπ/3 + 2e−4jπ/3
2π 2π 4π 4π
= 5 − cos − j sin + 2 cos − j sin
3 3 3 3
√ √
1 3 1 3
= 5− − − j +2 − +j
2 2 2 2
√
1 3 √
= 5+ + j−1+j 3
2√ 2
9 3 3
= + j
2 2
= 4.5 + 2.5981j
F [2] = f [n]e−4jnπ/3
4π 4π 8π 8π
= 5 − 1 cos − j sin + 2 cos − j sin
3 3 3 3
√ √
1 3 1 3
= 5− − +j +2 − −j
2 2 2 2
√
1 3 √
= 5+ −j −1−j 3
2√ 2
9 3 3
= − j
2 2
= 4.5 − 2.5981j
N −1
4. If F [k] = f [n]e−2jnkπ/n
n=0
Pearson
c Education Limited 2001
Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual 231
N −1
F [k] = f [n] e2jnkπ/N
n=0
(since if z = ejθ then z = e−jθ and z1 z2 = z1 · z2 ). If f [n] is real then f [n] = f [n]
and the result follows immediately.
5.
N −1
F [k] = f [n]e−2jnπk/N
n=0
N −1
F [k] = f [n]e2jnπk/N if f is real
n=0
N −1
F [N − k] = f [n]e−2jnπ[N −k]/N
n=0
= f [n]e−2jnπN/N e2jnπk/N
= f [n]e−2jnπ e2jnπk/N
= f [n]e+2jnπk/N since e−2jnπ = 1
= F [k] as required
Exercises 24.9.2
1.
N −1
1
f [n] = F [k]e2jknπ/N n = 0, 1, 2, . . . N − 1
N
k=0
Pearson
c Education Limited 2001
232 Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual
1 1
f [2] = F [k]ejkπ = (6 − 2(−1) + 2(1) − 2(−1))
4 4
1
= (12) = 3
4
1 1
f [3] = F [k]ejk3π/2 = 6 − 2ej3π/2 + 2ej3π − 2ej9π/2
4 4
1
= (6 + 2j − 2 − 2j) = 1
4
N −1
1
3. Consider F [k]e2jknπ/N
N
k=0
N −1
N −1
1
−2jmkπ/N
= f [m]e e2jknπ/N
N m=0
k=0
N −1 −1
1
N
= f [m] e−2jkπ(m−n)/N (∗)
N m=0
k=0
Now study this sum over m. As m varies between 0 and N − 1, for some value m will equal n. Consider this
first.
With m = n, this becomes
N −1
1 1
f [n] 1 = f [n]N (1)
N N
k=0
= f [n] (2)
N −1
Now consider any other value of m with m
= n. Consider e−2jkπ(m−n)/N
k=0
N −1 k
= e−2jπ(m−n)/N
k=0
N −1
= rk where r = e−2jπ(m−n)/N
k=0
= 1 + r + r2 + . . . rN −1
Pearson
c Education Limited 2001
Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual 233
This is a geometric progression with N terms, first term 1 and common ratio r.
1 1 − rN 1 1 − e−2jπ(m−n)
SN = =
1−r 1 − e−2jπ(m−n)/N
= 0 since e−2jπ(m−n) = 1 for m, n integers
Exercises 24.12
1. N = 4, W = e−jπ/2
W1 = e−jπ/2 = −j
W2 = j 2 = −1
W3 = j
..
.
W 9 = jjj = j 3 = −j
W0 W0 W0 W0
W0 W1 W2 W
3
W = 0
W W2 W4 W6
W0 W3 W6 W 9
1 1 1 1
1 −j −1 j
=
1 −1 1 −1
1 j −1 −j
1 1 1 1 1 3 2 4
1 −j −1 j 2 1 1 − 3j 4
F [k] = =
1 −1 1 −1 0 −1 0 0
1 j −1 −j −1 1 1 + 3j 4
Exercises 24.13
1. (a)
1 1 1 1 1 2 6 6
1 −j −1 j 2 1 −1 − j 1+j
=
1 −1 1 −1 2 1 0 0
1 j −1 −j 1 2 −1 + j 1−j
(b)
3
| f [n] |2 = 1 + 4 + 4 + 1 = 10
n=0
1 1 1
| F [k] |2 = {36 + (1 + 1) + 0 + (1 + 1)} = 40 = 10
4 4 4
Pearson
c Education Limited 2001
234 Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual
2.
f = 3 1 5 4
g = 2 −1 9 5
fg = 6 −1 45 20
(a) f g = 70
(b)
1 1 1 1 3 2 13 15
1 −j −1 j 1 −1 −2 + 3j −7 + 6j
F, G = =
1 −1 1 −1 5 9 3 7
1 j −1 −j 4 5 −2 − 3j −7 − 6j
(d)
1 1 280
F Ḡ = (195 + 32 + 21 + 32) = = 70
N 4 4
3.
N −1
F [k] = f [n]e−2jnkπ/N = D{f [n]}
n=0
N −1
D{f [n − i]} = f [n − i]e−2jnπk/N
n=0
N −1
= f [n − i]e−2jπk(n−i)π/N e−2jπki/N
n=0
−2jkπi/N
= e F [k]
N −1
This development assumes that F [k] = f [n − i]e−2jπk(n−i)/N .
n=0
−1−i
N
F [k] = f [p]e−2jπkp/N
p=−i
Pearson
c Education Limited 2001
Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual 235
4. Parseval’s theorem:
N −1 N −1
N −1
1 1
−2πjnk/N
F [k]G[k] = f [n]e G[k]
N N n=0
k=0 k=0
N −1 −1
1
N
= f [n] G[k]e−2πjnk/N (∗)
N n=0
k=0
N −1
1
but g[n] = G[k]e2πjkn/N
N
k=0
1
therefore g[n] = G[k]e−2πjkn/N
N
N −1
therefore (∗) becomes f [n]g[n]
n=0
Hence
N −1
1
f [n]g[n] = F [k]G[k]
N
k=0
(Parseval)
Exercises 24.14.1
Pearson
c Education Limited 2001
236 Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual
Note f ∗ g = −12, −12, 79, 65, 2, −5, the coefficients of this polynomial.
(b)
(9 − 8x)(1 + 2x − 4x2 ) = 9 +18x −36x2
−8x −16x2 +32x3
= 9 +10x −52x2 +32x3
f ∗ g = 9, 10, −52, 32.
3.
(1 − x + x2 + 3x3 )(7 + 2x + x3 ) = 7 +2x + 0x2 +x3
−7x −2x2 +0x3 −x4
7x2 +2x3 +0x4 +x5
21x3 +6x4 +0x5 +3x6
= 7 −5x +5x 2
+24x3 +5x4 +x5 +3x6
Hence f ∗ g = 7, −5, 5, 24, 5, 1, 3.
4.
∞
f ∗g = f [m]g[n − m] =
m=−∞ all m
Let n − m = p
f ∗g = f [n − p]g[p] = = g[p]f [n − p] = g ∗ f
all p
Exercises 24.14.2
1. The solution is developed in the following table.
f [m] 1 −1 1 3
n=0 g[−m] 1 0 2 7 1 0 2 12
n=1 g[1 − m] 1 0 2 7 1 0 −4
n=2 g[2 − m] 1 0 2 7 1 8
n=3 g[3 − m] 1 0 2 7 24
Hence f ∗ g = 12, −4, 8, 24.
Exercises 24.14.3
1.
1 1 1 1 1 7 4 10
1 −j −1 j 2 7−j
F, G = −1 = 4j
1 −1 1 −1 1 0 0 4
1 j −1 −j 3 1 −4j 7+j
F · G = 40, 4 + 28j, 0, 4 − 28j
Also
1 1 1 1 12 40
1 −j −1 j −4 4 + 28j
=
1 −1 1 −1 8 0
1 j −1 −j 24 4 − 28j
Pearson
c Education Limited 2001
Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual 237
So
D{f ∗ g} = F [k]G[k]
as required.
2.
f = 9, 0, 1
g = 5, 4, 5, 2, 1.
The linear convolution has length 3 + 5 − 1 = 7. Pad to give
f = 9, 0, 1, 0, 0, 0, 0
g = 5, 4, 5, 2, 1, 0, 0.
f [m] 9 0 1 0 0 0 0
n=0 g[−m] 0 0 1 2 5 4 5 0 0 1 2 5 4 45
n=1 g[1 − m] 0 0 1 2 5 4 5 0 0 1 2 5 36
n=2 g[2 − m] 0 0 1 2 5 4 5 0 0 1 2 50
n=3 g[3 − m] 0 0 1 2 5 4 5 0 0 1 22
n=4 g[4 − m] 0 0 1 2 5 4 5 0 0 14
n=5 g[5 − m] 0 0 1 2 5 4 5 0 2
n=6 g[6 − m] 0 0 1 2 5 4 5 1
f ∗ g = 45, 36, 50, 22, 14, 2, 1.
3. not provided
Exercises 24.14.4
1.
f [m] 4 5 9
n=0 g[m] 3 1 1 26
n = −1 g[m + 1] 3 1 1 9
n = −2 g[m + 2] 3 1 1 4
n=1 g[m − 1] 3 1 1 24
n=2 g[m − 2] 3 1 1 27
2.
∞
f g = m=−∞ f [m]g[m − n].
Let m − n = p.
∞
f g = p=−∞ f [p + n]g[p], p is a dummy variable.
∞
Hence, f g = m=−∞ f [m + n]g[m], as required.
Pearson
c Education Limited 2001
238 Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual
3.
m 0 1 2
g[m] 3 1 1
n=0 f [m] 4 5 9
n=1 f [m − 1] 0 4 5 9
n=2 f [m − 2] 0 0 4 5 9
n = −1 f [m + 1] 4 5 9 0
n = −2 f [m + 2] 4 5 9 0 0
n = 0: f [m]g[m] = 12 + 5 + 9 = 26.
n = 1: f [m − 1]g[m] = 4 + 5 = 9.
n = 2: f [m − 2]g[m] = 4.
n = −1: f [m + 1]g[m] = 15 + 9 = 24.
n = −2: f [m + 2]g[m] = 27.
The required sequence is then 27, 24, 26, 9, 4, obtained by taking the previous results in order.
m 0 1 2
f [m] 3 2 1
n=0 f [m] 3 2 1
4. n=1 f [m − 1] 0 3 2 1
n=2 f [m − 2] 0 0 3 2 1
n = −1 f [m + 1] 3 2 1 0
n = −2 f [m + 2] 3 2 1 0 0
Then f f = 3, 8, 14, 8, 3.
Exercises 24.14.6
1. f = 2, 3, −1, g = 8, 7, 1.
f [m] 2 3 −1
n=0 g[m] 8 7 1 36
n=1 g[m − 1] 1 8 7 1 19
n=2 g[m − 2] 7 1 8 7 1 9
f
g = 36, 19, 9.
F = 4, 1 − 3.4641j, 1 + 3.4641j.
G = 16, 4 − 5.1962j, 4 + 5.1962j.
F G = 64, 22 − 8.6603j, 22 + 8.6603j.
D−1 {F G} = 36, 19, 9.
This verifies the circular convolution theorem.
Pearson
c Education Limited 2001
Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual 239
2.
N −1 N
−1
D{f
g} = f [m]g[m − n]e−2πjkn/N
n=0 m=0
N −1
N −1
= f [m] g[m − n]e−2πjkn/N
m=0 n=0
let m − n = p
−1 m−(N −1)
N
= f [m] g[p]e−2πjk(m−p)/N
m=0 p=m
−1 m−(N −1)
N
−2πjkm/N
= f [m]e g[p]e2πpjk/N
m=0 p=m
= F [k]G[k]
as required. Note the sum over one period of a periodic sequence (and hence the second term is G[k]), and also
N −1
G[k] = g[n]e−2πjkn/N
n=0
and
N −1
G[k] = g[n]e2πjkn/N
n=0
N −1 N
−1
D{f
g} = f [m − n]g[m]e−2πjkn/N
n=0 m=0
N −1
N −1
= g[m] f [m − n]e−2πjkn/N
m=0 n=0
let m − n = p
−1 m−(N −1)
N
= g[m] f [p]e−2πjk(m−p)/N
m=0 p=m
−1 m−(N −1)
N
= g[m]e−2πjkm/N f [p]e2πjkp/N
m=0 p=m
= G[k]F [k]
Pearson
c Education Limited 2001
240 Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual
Review Exercises 24
1. (a)
1
F (ω) = (1 − t2 )e−jωt dt
−1
−jωt 1 1
2 e e−jωt
= (1 − t ) − −2t dt
−jω −1 −1 −jω
1 1 −jωt
2 te−jωt e
= − − dt
jω −jω −1 −1 −jω
−jωt
1
2 e−jω + ejω e
= − +
jω −jω ω 2 −1
4 cos ω 4 sin ω
= − +
ω2 ω3
(b)
π
F (ω) = sin t e−jωt dt
−π
π
1
= e(j−jω)t − e(−j−jω)t dt
2j −π
π
1 ej(1−ω)t e−j(1+ω)t
= −
2j j(1 − ω) −j(1 + ω) −π
j sin(1 − ω)π sin(1 + ω)π
= − +j
1−ω 1+ω
j sin ωπ sin ωπ
= − −j
1+ω 1−ω
2j sin ωπ
= −
1 − ω2
c)
τ
F (ω) = e−jωt dt
0
−jωt
τ
e
=
−jω 0
cos ωτ − j sin ωτ − 1
=
−jω
sin ωτ (1 − cos ωτ )
= −j
ω ω
d)
0 ∞
F (ω) = −e (α−jω)t
dt + e(−α−jω)t dt
∞ 0
Pearson
c Education Limited 2001
Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual 241
0 (−α−jω)t
∞
−e(α−jω)t e
= +
α − jω −∞ −α − jω 0
1 1
= − +
α − jω α + jω
−2jω
=
α2 + ω 2
2. (a)
2
F (ω) = 3te−jωt dt
−2
2
3te−jωt 3e−jωt
2
= − dt
−jω −2 −2 −jω
−jωt
2
6e−2jω + 6e2jω 3e
= +
−jω ω 2 −2
6
= (2jω cos 2ω − j sin 2ω)
ω2
(b)
2
F (ω) = 6 e−jωt dt
0
2
e−jωt
= 6
−jω 0
−2jω
(e − 1)
= 6
−jω
6
= (sin 2ω + j cos 2ω − j)
ω
3. (a)
∞
F{f (t)} = f (t)e−jωt dt
−∞
∞
∞
= e−jωt f (t) −∞ − f (t)(−jω)e−jωt dt
−∞
= jωF (ω)
∞
F{f (at)} = f (at)e−jωt dt
−∞
1 ∞
= f (u)e−jωu/a du
a −∞
1 ω
= F
a a
Pearson
c Education Limited 2001
242 Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual
5.
(i)
∞ ∞
F (ω) = f (t)e−jωt dt F (0) = f (t)dt
−∞ −∞
(ii)
∞ ∞
1 1
f (t) = F (ω)ejωt dω → f (0) = F (ω)dω
2π −∞ 2π −∞
(iii)
∞ ∞ ∞
F (ω) = f (t)e−jωt dt = f (t) cos ωt dt − j f (t) sin ωt dt
−∞ −∞ −∞
= even function − j odd function
∞
= 2 f (t) cos ωt dt if f is even
0
6. not supplied
7.
2α
f (t) = e−α|t| F (ω) =
α2 + ω 2
Then, from the t − −w duality principle,
1 π −α|ω|
F = e
α + t2
2 α
Hence ∞
cos bt π −αb πe−αb
2 2
dt = F (0) = e + e−αb =
−∞ α +t 2α α
Pearson
c Education Limited 2001
Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual 243
8.
1 1 1 1 3 9
1 −j −1 j 3 3
=
1 −1 1 −1 0 −3
1 j −1 −j 3 3
|f [n]|2 = 9 + 9 + 9 = 27
1 1
|F [k]|2 = (81 + 9 + 9 + 9)
N 4
1
= (108)
4
= 27
9.
(3 − x − 7x2 )(4 + 0x + 12 x2 ) = 12 + 0x + 32 x2
−4x +0x2 − 12 x3
−28x2 +0x3 − 72 x4
12 −4x − 53
2 x
2
− 12 x3 − 72 x4
f ∗ g = 12, −4, − 53
2 , −2, −2.
1 7
and
∞
∞
t(−−jω) et(−−jω)
e dt =
0 −* − jω 0
Then
∞
0
b
−et(−jω) et(−−jω)
sgn (t)e−jωt dt = lim +
−∞ →0,b→∞ * − jω −b −* − jω 0
1 e−b(−jω) eb(−−jω) 1
= lim − + + −
→0,b→∞ * − jω * − jω −* − jω −* − jω
1 1
= lim − +
→0 * − jω * + jω
−2jω
= lim
→0 *2 + ω 2
2j
= −
ω
2
=
jω
as required.
Pearson
c Education Limited 2001
244 Croft,Davison and Hargreaves,Engineering Mathematics,Solutions Manual
2
2π sgn (−ω) is the Fourier transform of
jt
So ∞
2 −jωt
e dt = 2πsgn (−ω)
−∞ jt
and by rearranging the constants ∞
1 −jωt
e dt = jsgn (−ω)
−∞ πt
Also the signum function is odd and hence this last expression can be written −jsgn (ω).
(c)
From the convolution theorem
f (t) ∗ g(t) = F −1 {F (ω)G(ω)}
Take f (t) = 1
πt . Then F (ω) = −jsgn(ω). Take g(t) = cos αt. Then G(ω) = π(δ(ω + α) + δ(ω − α)).
Then
1
∗ cos αt = F −1 {−jsgn(ω)π(δ(ω + α) + δ(ω − α))}
πt
11.
N −1
N −1
f [n]
g[−n] = f [m]g[−(m − n)] = f [m]g[n − m] = f [n]
∗ g[n]
m=0 m=0
Pearson
c Education Limited 2001